医療翻訳アプリ開発における外国人ユーザビリティテスト実施結果 - 友久, 甲子 (Transactions of Japanese Society for Medical and Biological Engineering, 2015)
Although there is a growing emergence of translating and interpreting services for non-Japanese speakers recently, the reality is that quality varies greatly. Yet such services in the field of medical care must be high in quality, for they are concerned with one's health and life. Therefore, the author conducted a usability testing of a pharmacy translating application that is being developed in six languages to find the necessary procedures and perspectives for guaranteeing quality when developing translating services in the field of medical care. In the test, six non-Japanese subjects were asked to test out the application. They were audio and video recorded, which were analyzed alongside interviews which were conducted to find reasons for the problems they experienced. The results suggested that the greatest factor behind their dissatisfaction was the difference in culture and medical systems between Japan and that of the subjects' native country. The author concludes that it is essential to listen to opinions from non-Japanese speakers and recognize such differences to guarantee quality when developing translating services in the field of medical care.